Nighttime transpiration in woody plants from contrasting ecosystems - Dawson, T; Burgess, S; Tu, K; Oliveira, R; Santiago, L; Fisher, J; Simonin, K; Ambrose, A (Oxford University Press, 2007)
It is commonly assumed that transpiration does not occur at night because leaf stomata are closed in the dark. We tested this assumption across a diversity of ecosystems and woody plant species by various methods to explore the circumstances when this assumption is false. Our primary goals were: (1) to evaluate the nature and magnitude of nighttime transpirations, En, or stomatal conductance, gn; and (2) to seek potential generalizations about where and when it occurs. Sap-flow, porometry and stable isotope tracer measurements were made on 18 tree and eight shrub species from seven ecosystem types. Coupled with environmental data, our findings revealed that most of these species transpired at night. For some species and circumstances, nighttime leaf water loss constituted a significant fraction of total daily water use. Our evidence shows that En or gn can occur in all but one shrub species across the systems we investigated. However, under conditions of high nighttime evaporative demand or low soil water availability, stomata were closed and En or gn approached zero in eleven trees and seven shrub species. When soil water was available, En or gn was measurable in these same species demonstrating plasticity for En or gn. We detected En or gn in both trees and shrubs, and values were highest in plants from sites with higher soil water contents and in plants from ecosystems that were less prone to atmospheric or soil water deficits. Irrespective of plant or ecosystem types, many species showed En or gn when soil water deficits were slight or non-existent, or immediately after rainfall events that followed a period of soil water deficit. The strongest relationship was between En or gn and warm, low humidity and (or) windy (>0.8 ms⁻¹) nights when the vapor pressure deficit remained high (>0.2 kPa in wet sites, >0.7 kPa in dry sites). Why En or gn occurs likely varies with species and ecosystem type; however, our data support four plausible explanations: (1) it may facilitate carbon fixation earlier in the day because stomata are already open; (2) it may enhance nutrient supply to distal parts of the crown when these nutrients are most available (in wet soils) and transport is rapid; (3) it may allow for the delivery of dissolved O₂ via the pernchyma to woody tissue sinks; or (4) it may occur simply because of leaky cuticles in older leaves or when stomata cannot close fully because of obstructions from stomatal (waxy) plugs, leaf endophytes or asymmetrical guard cells (all non-adaptive reasons). We discuss the methodological, ecophysiological, and theoretical implications of the occurence of En or gn for investigations at a variety of scales.